A Political Journey: Brecht’s Distancing Effect as Transforming Proposal of Russian Formalism’s Defamiliarization (Castilla. Estudios de Literatura, 2016)
In the two first decades of the 20th century, one of the main discoveries of the Russian formalism in their search of literariness is the defamiliarization. This concept place the purpose of literature on estrangement or on the impossibility of automatism. Two decades later, Bertolt Brecht go back to the concept to transform it into the distancing effect which impede the public’s identification with the performed fiction. In this article, we follow the evolution of the defamiliarization, positioned at the hearth of the discussion between formalism and socialist realism initiated on the USSR’s first years, experiencing an aftershock in the German Democratic Republic in the fifties. This itinerary demonstrate the close relation between the dialectic processes of politic and literary systems belonging to the dynamic reality described by Even-Zohar in his polysystem theory.
Keywords: Russian formalism; defamiliarization; Bertolt Brecht; distancing effect; polysystem theory; socialist realism